STUDI TENTANG PENGARUH ORIENTASI PASAR TERHADAP KINERJA PERUSAHAAN BATIK SKALA KECIL DAN MENENGAH DI PEKALONGAN - Imawati, Ditha (Master of Management Diponegoro University, 2013)
The level of batik sales is recognized by a number entrepreneurs of batik in Pekalongan increased in 2010 after a recognized batik as an Indonesian cultural heritage by UNESCO in late 2009. After that, batik sales decreased due to a lot of batik industries that have sprung up in other cities in Indonesia. This conditions makes each batik SMEs must be able to survive and develop their business.This study tried to analyze the effect of market orientation on capacity to innovate and new product performance and also the influence of both variables to improve the business performance. The sampling technique used in this study is the purposive sampling method. Respondents who used as many as 139 respondents are owners, managers, and owners as well as managers of small and medium-scale indrusties batik ini Pekalongan with a minimum age of 20 years.The test results of the five hypotheses prove there is a hypothesis that is rejected. Based on this research can be concluded that market orientation can enhance capacity to innovate and both of variables can improve the new product performance so as to achieve the business performance. While the capacity to innovate is not shown to affect the improvement of business performance. This study provides some limitations of the study and future research agenda that can be done on advanced research.